SIGNAGE AS A MEDIUM TO STRENGTHEN CULTURAL IDENTITY: A CASE STUDY AT KAMPUNG BUDAYA SINDANG BARANG BOGOR - Utami, Winda; Kharisma, Vidya (Lembaga Penelitian Universitas Pasundan, 2025)
Signage plays an important role in cultural heritage destinations, functioning not only as wayfinding tools but also as communicative devices that reflects the cultural identity of a place. In many regions, signage has evolved into a medium for cultural storytelling through the use of local language, symbols, and traditional elements. However, in several heritage sites in Indonesia, the cultural integration of signage remains underdeveloped. This study investigates how signage contributes to the communication of cultural identity in Kampung Budaya Sindang Barang, one of the oldest traditional villages in Bogor. Despite its active role in preserving Sundanese tradition through rituals, architecture, and educational programs, the village’s existing signage remains limited in both quantity and cultural representation. This research employs qualitative case study approach, using observation, interviews, and documentation to explore signage functions within the village. Analysis was conducted using a SWOT matrix to identify internal and external factors, while the pyramid signage model was applied to examine signage through its information content, graphic, and hardware system. The findings reveal that the current signage primarily fulfills functional purposes such as navigation and regulation, without incorporating Sundanese language, symbols or motifs. This lack of cultural representation reduces signage effectiveness in communicating identity and engaging visitors. The result demonstrates a significant gap between the cultural richness of the site and its ability to express identity through design. This study contributes to a deeper understanding of how signage can serve as a medium for cultural expression and calls attention to the need for contextually relevant signage in heritage tourism destination. Keywords: Cultural Identity, Cultural Village, Signage, Sunda